Facile construction of peptidomimetics by sequential C–S/C–N bond activation of Ugi-adducts. Issue 24 (5th November 2021) - Liu, Chao; Song, Liangliang; Peshkov, Vsevolod A.; Van der Eycken, Erik V.
Abstract : Diverse peptidomimetics containing a primary amide are prepared via the integration of an Ugi-4CR and sequential C–S/C–N bond activation. Abstract : A novel selectively sequential C–S/C–N bond activation is presented. Through the combination of an Ugi-4CR and sequential C–S/C–N bond cleavage, diverse peptidomimetics containing a primary amide are prepared in a rapid, highly efficient and step-economical manner. This approach exhibits high yield, excellent chemoselectivity and functional group tolerance. Compounds derived from the pharmaceuticals febuxostat, probenecid and memantine as well as β-amino acid are prepared. This method provides a new direction for the synthesis of peptidomimetics.